PROFITABILTAS DAN KELAYAKAN USAHATANI PADI SAWAH TADAH HUJAN (Studi Kasus Kelurahan Jagona Kecamatan Pangkajene Kabupaten Pangkep) - Arifin Arifin (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
The implementation of farming carried out by farmers must have the right considerations in production in order to obtain the best profit. The best or maximum profit is achieved when the level of production is optimal. To obtain the optimal level of production, producers must take into account the amount of production that is in a position of balance or profit. The purpose of this study was to analyze the profitability and feasibility of rainfed rice farming. This research was conducted in Jagona Village, Pangkajene District, Pangkep Regency. The research population was 148 people and 20% of the population were taken as research samples, namely 30 farmers. Farmer samples were taken using simple random sampling method. Data collection techniques used are observation, interviews, and documentation. The types of data are qualitative and quantitative data. There are data sources, namely primary and secondary data. The data analysis method used is the analysis of profitability and feasibility of farming. The results of this study indicate a Return on Investment (ROI) of 134.24% > 50% (profit), Break Event Point (BEP) of Rp. 699.310.11 < Rp. 8,689,083.33 (feasible), and Profitability of 134.24% > 3% (feasible). Rainfed lowland rice farming in Jagona Village, Pangkajene District, Pangkep Regency is feasible and profitable